Cortical thickness and its relationship to cognitive performance and metabolic control in adults with phenylketonuria. Issue 6 (27th September 2022) - Muri, Raphaela; Maissen‐Abgottspon, Stephanie; Rummel, Christian; Rebsamen, Michael; Wiest, Roland; Hochuli, Michel; Jansma, Bernadette M.; Trepp, Roman; Everts, Regula
Abstract: Despite good control of phenylalanine (Phe) levels during childhood and adolescence, adults with phenylketonuria (PKU) often show abnormalities in the white matter of the brain, which have been associated with poorer cognitive performance. However, whether such a relationship exists with cortical gray matter is still unknown. Therefore, we investigated cortical thickness and surface area in adults with early‐treated PKU and their relationship to cognitive functions and metabolic control. We included 30 adult patients with early‐treated and metabolically well‐controlled PKU (median age: 35.5 years) and 54 healthy controls (median age: 29.3 years). Surface‐based morphometry was derived from T1‐weighted magnetic resonance images using FreeSurfer, and general intelligence, executive functions, and attention were assessed. Concurrent plasma Phe, tyrosine, and tryptophan levels were measured in patients. In addition, Phe levels were collected retrospectively to calculate the index of dietary control. Patients showed a thinner cortex than controls in regions of the bilateral temporal, parietal, and occipital lobes (effect size r = −0.34 to −0.42, p < 0.05). No group differences in surface area were found. In patients, accuracy in the working memory task was positively correlated with thickness in the left insula ( r = 0.45, p = 0.013), left fusiform gyrus ( r = 0.39, p = 0.032), and right superior temporal gyrus ( r = 0.41, p = 0.024), but did not survive false discovery rate correction. Neither concurrent nor historical metabolic parameters were related to cortical thickness. Taken together, adults with PKU showed widespread reductions in cortical thickness despite good metabolic control in childhood and adolescence. However, alterations in cortical thickness were unrelated to metabolic parameters and cognitive performance. Abstract :